MEASURING TECHNICAL EFFICIENCY OF MALAYSIAN REAL ESTATE INVESTMENT TRUSTS: A DATA ENVELOPMENT ANALYSIS APPROACH - Chuweni, Nor Nazihah (PLANNING MALAYSIA, 2019)
The research examines the technical efficiency (TE) and economies of scale for the Malaysian Real Estate Investment Trust (M-REITs) from 2010 to 2014, using a non-parametric approach of Data Envelopment Analysis (DEA). The nonparametric approach of Variable Return to Scale DEA (VRS-DEA model) was used to estimate the efficiency scores for M-REITs. The negative inefficient value for the technical inefficiencies is identified as a result of both poor input utilisation (managerial inefficiency) and failure of M-REITs to operate at optimum scale (scale inefficiency). The mean technical efficiency (TE) measures ranged from as low as 41.70% in 2011 to as high as 84.30% in 2014. Despite having the Sharia requirement, Islamic REITs in Malaysia provide an effective investment opportunity evidenced by the higher scores for all efficiency measures, as compared to conventional REITs for the period under study. Pure technical inefficiency has a greater deviation in the efficient frontier than scale inefficiency, suggesting that M-REITs inputs are not fully minimised to produce more outputs. With regard to scale inefficiency, M-REITs are operating at economies of scale, indicating the importance of expansion or growth to improve on efficiency performance. This will then allow M-REIT managers to formulate better strategic investment decisions.